Kaposiform Hemangioendothelioma in a 3 Months Old Infant - Uppuluri, Ramya (Indian J Hematol Blood Transfus, 2016)
Kaposiform hemangioendothelioma is a rare, highly vascular and aggressive soft tissue tumor frequently associated with Kasabach–Merritt phenomenon, usually seen in early infancy. Early diagnosis by means of MRI and tissue biopsy portends a better outcome. Treatment includes surgical excision when feasible and medical management with steroids, propranolol, vincristine and supportive treatment for coagulopathy. We report a 3 months old female infant who was diagnosed, treated successfully and is now in complete remission.